(3cJGH GdMGFWs - (3GdMfaj GdNQGSGfj, CHh eMeO, GdnqUrOQ GdnqTpgjO, HQgGf GdCFeI, YeQ Hf YHO GdYRjR Hf YeQ Hf eGRI, (B536 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd GdUOQ GdEeGe GdTgjO MSGe GdOjf SjO GdTgOGA GdMeO ddg Ydi fYeg GdXGgQI hHYO aEfj hLOJ eSGFd OYhi GdMjWGf hGdWQb heSjd GdeGA ef CUYH GdeSGFd eQGeG hcGf jJLdLd aj UOQj Cf CLeY eG JaQb ef cJH CUMGHfG ef eSGFdgG MJi hLOJ LeYG ajgG ddTjN GdeQLi Gdfbaj TQM bGVj GdbVGI CHj YHO Gddg GdHNGQj (B-- (3dcfg eaJbQ Edi GdJgPjH hGdJfbjM (B-- (3aJeeJ eG gfGdc s
(3BNQgG (B:s
(3GdaUd GdKGfj (B: (3Yjf eGA Ch HFQ eGA Hjf QLdjf hgh TQH dgeG aGMJGLJ Edi JfbjI Ch YeGQI aGeJfY CMOgeG ef GdfabI YdjgG gPg GdeSCdI Ydi SHjd GdGjJbUGA cJHGgG aj TQM GdfabGJ ddNUGa s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 51s
(3eYLe GdeDdajf (B2 / 562s
(3cTa GdXfhf (B2 / 1414s
(3GdLhGgQ GdeVjI (B1 / 391s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs